Topochemical engineering of composite hybrid fibers using layered double hydroxides and abietic acid - Sobhana, Liji; Kesavan, Lokesh; Gustafsson, Jan; Fardim, Pedro (Beilstein Journal of Nanotechnology, 2019)
Topochemical engineering of hybrid materials is an efficient way of synthesizing hydrophobic and highly tensile fiber composites by utilizing the intermolecular hydrogen bonds in natural materials. These materials include wood pulp fibers, abietic acid (resin acid) and inexpensive metal salts. In this work, a hybrid composite was created using bleached and unbleached kraft pulp fibers as cellulose platform. In situ co-precipitation of layered double hydroxide (LDH) was performed to grow LDH crystals on the surface of the cellulose fibers, followed by the immobilization of abietic acid (AA) on LDH-grafted cellulose. Here we aimed to benefit from the hydrogen bonding between –OH groups of cellulose and LDH, and the –COOH groups of AA to obtain charge-directed assembly of one material on the other material. Thus, composite hybrid fibers (C-HF) were produced and then characterized by optical (CAM), spectroscopic (XRD, IR) and microscopic techniques (SEM) to determine their average length and distribution, structure and purity, bonding, and morphology. These fibers further were tested for water contact angle (hydrophobicity), oil absorption (lipophilicity), tensile strength and ISO brightness measurements. The performance of C-HF was compared with unmodified reference fibers (REF), fibers composed with only AA (C-F) and LDH-hybridized fibers (HF). The results revealed a variety of correlations between materials and their properties due to characteristic surface morphology, functional groups, hydrogen bonding and natural co-materials such as lignin and hemicelluloses. Attractive and repulsive van der Waals forces between material entities play a crucial role in the resulting properties.
Keywords: abietic acid; composite hybrid fibers; high tensile pulp; hydrophobic pulp; layered double hydroxides